Rancang Bangun Sistem Pengendalian Lampu Otomatis Berbasis Arduino UNO Sebagai Alat Peraga Fisika Dasar Pada Hukum Ohm - Zhahrotun Nurroniah; Nadiah Putri Anggraeni; I’lman Hadi Asy’ari; Devita Syafa Adisti Putri; Safina Aulia Sani; Alex Harijanto; Subiki . (Peneliti.net, 2023)
Arduino UNO design is a series that is carried out through processes to make automatic lights by designing, making device prototypes, implementing, and testing the final device until the device is complete and ready to be tested. The purpose of this research is to develop a prototype of basic physics teaching aids on the subject of Ohm's law. The method used in this research is the research and development method. The results obtained in this study are that the Arduino uno-based automatic light control circuit can be used as a basic physics teaching aid for Ohm's law material. This trainer uses 4 lights that are assembled in series and parallel. In addition, this trainer is accompanied by Bluetooth to connect with an Android smartphone as a light switch controller.